2013
DOI: 10.1037/a0032672
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and emotion coherence: Evidence for strategy-specific effects.

Abstract: One of the central tenets of emotion theory is that emotions involve coordinated changes across experiential, behavioral, and physiological response domains. Surprisingly little is known, however, on how the strength of this emotion coherence is altered when people try to regulate their emotions. To address this issue, we recorded experiential, behavioral, and physiological responses while participants watched negative and positive pictures. Cross-correlations were used to quantify emotion coherence. Study 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…This finding may be interpreted within the context of a growing literature suggesting that humans may have the capacity to invoke substantive influence over the nature of their neural responses to specific stimulus types, including emotionally-valent pictures [15], [31], pain [32], stimuli that evoke craving [33], and during the processing of happy memories [34]. The ability to modulate neural activity to negative feedback may have particularly practical implications, however.…”
Section: Discussionmentioning
confidence: 79%
“…This finding may be interpreted within the context of a growing literature suggesting that humans may have the capacity to invoke substantive influence over the nature of their neural responses to specific stimulus types, including emotionally-valent pictures [15], [31], pain [32], stimuli that evoke craving [33], and during the processing of happy memories [34]. The ability to modulate neural activity to negative feedback may have particularly practical implications, however.…”
Section: Discussionmentioning
confidence: 79%
“…Fourth, stimuli representing different discrete negative emotions show a moderate degree of temporal coherence between subjective and neurophysiological responses, such that both phenomenon tend to unfold on similar time courses [29]. Recent evidence suggests that emotion regulation strategies may disrupt this temporal coherence between physiological and subjective responses [30]; however, some strategies are more prone to disrupt coherence than others (e.g., suppression > acceptance). It is unclear whether successful emotion regulation requires disruption of the coherence of emotion responses across subjective, physiological, and behavioral domains or if some strategies are more effective than others because they cause such disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have indicated that acceptance leads to decreases in negative emotions, relative to other experimental groups (Levitt, Brown, Orsillo, & Barlow, 2004; Wolgast et al, 2011), others have found no differences (Dan-Glauser & Gross, 2013; Dunn, Billotti, Murphy, & Dagleish, 2009). Indeed, a meta-analysis of laboratory studies of emotion regulation found that acceptance does not exert a reliable effect on negative emotions (Kohl, Rief, & Glombiewski, 2012).…”
Section: Acceptancementioning
confidence: 94%